FAKTOR PENENTU BRAND EQUITY DAN PENGARUHNYA PADA PURCHASE INTENTION - Evo Sampetua Hariandja; Aurellia Adeline; Ferdinandus Eric; Yossel Christopher (Ultima Management : Jurnal Ilmu Manajemen, 2021)
Abstract- This study aims to determine the effect of brand popularity on brand loyalty, brand awareness, perceived quality and brand reputation among Etude House Indonesia users. Other objective of this study are to t he effect of brand loyalty, brand awareness, perceived quality and brand reputation on brand equity. The effect of brand equity on purchase intention To address the objectives of the study, a quantitative research design was implemented by distributing the questionaires to 360 Etude House Indonesia users and implementing the intruments that fulfilled the validity and reliability test requriements. The data were analyzed by SEM SmartPLS 3. The findings revealed that there was an effect of Brand popularity affects brand awareness, perceived quality, and brand reputation. Other results show that the counrry of brand origin affects brand loyalty, brand awareness and brand perceived quality. Also, Brand equity is determined by brand loyalty and brand reputation. While Brand equity has a significant effect on purchase intention. In addition, brand equity also impacts on purchase intention. However, in this study the relationship of brand popularity to brand loyalty, the effect of country of brand origin on brand reputation, the effect of brand awareness on brand equity and the effect of perceived quality on brand equity is not supported in hypothesis testing. Keywords: Brand Popularity; Country of Brand Origin; Brand Loyalty, Brand Awareness; Perceived Quality; Brand Reputation; Brand Equity; Purchase Intention